Podwyższenie kapitału zakładowego bez zmiany umowy spółki — problem prawa pierwszeństwa - Chylicki, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article relates to the increase of share capital in limited liability company spółka z ograniczoną odpowiedzialnością without altering the articles of association. Particularly, the article encompasses the subject whether it is admissible to restrict the pre-emptive right of current shareholders to subscribe shares in increased capital in the procedure of “simplified increase of capital,” arguments against such admissibility raised both in legal literature and judical opinions and arguments in favor of such admissibility. The thesis presented in the article is that the restriction of exclusion of pre-emptive right of current shareholders is de lege lata admissible in the procedure of “simplified increase of share capital.”
Keywords: podwyższenie kapitału zakładowego; prawo poboru; ochrona akcjonariuszy; wyłączenie prawa poboru; kodeks spółek handlowych